ANALISIS PENINGKATAN DAYA SAING EKSPOR UMKM CENDERAMATA DI JAKARTA - Wulandari, Respati; Polla, Johanes Ronaldy; Novita, Novita (Jurnal Ekonomi : Journal of Economic, 2016)
Souvenir export done by SME in Jakarta has been done since the last few years, but this great business potential has not been done well. Hence, the purpose of this research is to analyze the strategy that SME needs to apply in improving the competitiveness of export products (souvenirs) in Jakarta, considering that competition in Asia is tighter in this MEA era. Analysis is done by viewing internal and external factors, and then strategy mapping is done by Ansoff Matriks so we obtain the best strategy for SME in improving its competitiveness, especially in increasing exports. Analysis result using Ansoff Matriks suggests product development strategy as the best one. With this strategy, SME will be able to maintain or even gain more customers, and also gain its competitiveness.Â Kata kunci : Competitiveness, SME, Export